IFITM3‐specific antibody reveals IFN preferences and slow IFN induction of the antiviral factor IFITM3 in humans - Wellington, D; Yin, Z; Abdel-Haq, A; Zhang, L; Forbester, J; Kite, K; Rajapaksa, U; Laurenson-Schafer, H; Makvandi-Nejad, S; Jin, B; Bowes, E; Manoharan, K; et al. (Wiley, 2020)
Using a specific antibody, we found that expression of the viral restriction factor IFITM3 differs across cell types within the immune compartment with higher expression in myeloid rather than lymphoid cells. IFITM3 expression was increased following IFN stimulation, mostly type I, in immune cells, with the exception of T cells.